Exercise and exposure to heat following bovine colostrum supplementation: a review of gastrointestinal and immune function - Carrillo, A. E.; Koutedakis, Y.; Flouris, A. D. (Cellular and Molecular Biology, 2013)
Colostrum is the first milk produced by mammalian mothers and is essential for the health and survival of the newborn. Bovine colostrum (BC) has greater concentrations of the bioactive components (i.e. immune and growth factors) than those found in human colostrum. As a result, BC supplementation has been recently adopted by many sport competitors as a means of enhancing immune function as well as improving performance. Improvements in physical performance associated with BC supplementation may stem from the ability of BC to maintain gastrointestinal (GI) integrity by decreasing GI permeability. During exercise in the heat, blood flow to the GI tract is reduced that leads to endotoxin leakage into circulation. Endotoxins, such as lipopolysaccharide, can trigger an inflammatory cascade leading to physiological strain that, in turn, increases heat storage and decreases time to exhaustion. GI permeability is lessened during passive heat stress following BC supplementation, but the influence of BC supplementation on GI function during exercise heat stress remains to be determined. The implications of endotoxemia during exercise in the heat is a matter of growing importance and warrants further study given the global increase in ambient temperatures during sport competitions.